Prehospital Trauma Management: Evaluation of a New Designed Smartphone Application - Fatemeh Taziki Balajelini; Tahereh Najafi Ghezeljeh (Iran University of Medical Sciences, 2018)
Background: Regarding the undeniable role of nurses in caring for patients with trauma, a suitable method is required for the education of nursing students to meet their needs. In this study, first we designed an educational smartphone application for pre-hospital trauma management and then nursing students evaluated its usefulness.  Methods: This applied study has a cross-sectional design and conducted to develop a mobile application. A total of 41 undergraduate nursing students participated in this study. They were selected through the census method from Iran University of Medical Sciences in 2018. The educational content of the application was developed based on the available standard skills required for prehospital trauma management. The study sample first received routine education. Then they used the application to handle and manage care for traumatic patients for one month. The students' satisfaction with the application was measured using a software called application satisfaction questionnaire. The obtained data were analyzed by descriptive statistics in SPSS V. 21. Results: After designing the application, 97.6% of the students reported that the classification of data in the application was appropriate. From their point of view (92.7%), the application also provided the required information for the appropriate patient's care in trauma situations. All students reported that the application, its links to web pages, movies, texts, and images were easy to use. About 95% of the students reported that graphic components, colors, and moving between pages were easy. Most were satisfied with the application and recommended its use to other undergraduate nursing students. The majority of them (80.5%) used the application consistently and suggested (80.5%) that the same application should be prepared for other courses.  Conclusion: The application was reported to be easy to use for trauma management and students were generally satisfied. Therefore, it can be used to facilitate the educational process and help students learn at any time and place.